THE RESPONSE OF FORMER TERRORISM PRISONERS TO THE ASSISTANCE OF THE INSAN CITA FOUNDATION THROUGH THE TECHNICAL GUIDANCE PROGRAM IN MAKASSAR CITY - Agus Samsono; Mutiah Sholehah (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
Muslims have a misunderstanding of the ideology of terrorism with the doctrine of jihad. The Islamic community does not have the power to understand their own religion, because there are people who give knowledge to themselves who are wrong about Islam, so that the community gets a misunderstanding about jihad. Terrorism is an event that worries all nations in the world, including Indonesia. Cases of terrorism have led to the emergence of government programs in an effort to deradicalize terrorists so that they no longer commit the same crimes. One of the efforts of the government and social welfare institutions is through the technical guidance program. The purpose of this study was to determine the response of former terrorist convicts to the assistance of the Insan Cita Foundation through the Bimbtek Program in Makassar City. The research method used is qualitative method. The results of the study indicate that the response of former terrorism convicts to the Insan Cita Foundation assistance through a technical guidance program in Makassar City, from a cognitive perspective, ex-terrorism convicts are able to recognize the program being followed. Then from the affective aspect, it can be seen with the feelings of former terrorism convicts who are quite satisfied with the technical guidance program. And from a conative perspective, ex-terrorism convicts have been able to determine their attitude about what to do after this technical guidance program is implemented. As for the mentoring stage, this research is more inclined to the facilitation stage because this program provides guidance and capital facilities for ex-terrorism convicts as program participants.